(untitled) (Sebha University Conference Proceedings, 2022)
This study dealt with the corrupt social convention in the penalty of self-aggression by premeditated murder, in terms of the causes of its appearance, its manifestations, and the consequences of its application in Libyan society and the violation of many of this custom, whether in terms of pardoning it, or from fulfilling the rules of Islamic Sharia, which came to be preserved. People have their lives, and their rights are preserved for them, which leads to the application of this corrupt custom to the corruption of society, in terms of disrupting a legal ruling such as forcing the blood guardians of the victim to give up their rights under the weight of social embarrassment, or prejudice and deception in the application of that custom, which generates resentment. Employing such custom in society to protect those who were deliberately guilty becomes a legislator for him, who will tread in this approach that violates on lives, and kills people unjustly and aggressively. Such action leads to the corruption of society by disrupting the law regulating it in criminal cases, then clarifying the legal ruling regarding the application of this corrupt social custom, and finding some solutions to limit its application in society.